Program Penyuluhan Kebersihan Dan Infrastruktur Sebagai Wujud Inovasi Dalam Membangun Kewirausahaan Masyarakat - Nopiyanti, Penti; Rosandy, Muhammad Wahyu; Nupsi, Nupsi; Ulva, Marya; Yolanda, Dwi; Nasution, Suswati; Soleh, Ahmad; Yulianti, Liza (Universitas Dehasen Bengkulu, 2025)
Community service is one form of implementation of the Tri Dharma of Higher Education which aims to improve community welfare through innovation-based empowerment. This program aims to develop community entrepreneurship through cleanliness counseling and infrastructure installation which includes painting portals, installing signs, and implementing community gymnastics and neighborhood association gatherings. This activity was carried out in RT.23, Pematang Gubernur Village, by involving the local community in every stage of its implementation. Cleanliness counseling is carried out to increase public awareness of the importance of maintaining a healthy and clean environment, while the installation of infrastructure is expected to strengthen local economic identity and independence. Community gymnastics and gatherings are a means to build solidarity and encourage active community participation in social activities. This program also functions as a forum to introduce the concept of community-based entrepreneurship through social innovation that can improve the quality of life and empower communities to be more economically independent. The expected results of this program are increased public awareness of the importance of environmental cleanliness, the creation of infrastructure that supports economic activities, and the formation of sustainable social entrepreneurs.